Provably secure verifiable multi‐stage secret sharing scheme based on monotone span program. (1st November 2017) - Mashhadi, Samaneh; Hadian Dehkordi, Massoud; Kiamari, Niloofar
Abstract : In multi‐secret sharing (MSS) scheme, a dealer distributes multiple secrets among a set of participants, each of them according to an access structure. In this study, the authors propose a novel linear MSS with computational verifiability that provide many functions for practical applications in comparison with the previous works focusing on MSS schemes in the general scenario. This scheme has the same advantages as previous schemes; moreover, it is verifiable and multi‐use secret sharing. Furthermore, in this scheme the secret reconstruction is according to the dealer's preassigned order. Also, they prove the security of the authors' scheme in the standard model.